Anti-inflammatory activities of Coleus forsteri (formerly Plectranthus forsteri) extracts on human macrophages and chemical characterization - Nicolas, Mael; Lasalo, Malia; Chow, Sharron; Antheaume, Cyril; Huet, Karl; Hnawia, Edouard; Guillemin, Gilles J.; Nour, Mohammed; Matsui, Mariko (Frontiers in Pharmacology, 2023)
Formerly named Plectranthus forsteri, Coleus forsteri (Benth.) A.J.Paton, 2019 is a Lamiaceae traditionally used to treat flu-like symptoms and shock-related ecchymosis, especially in the Pacific region. Few studies investigated chemical composition and anti-inflammatory potential of this plant. Herein, we investigated anti-inflammatory potential of C. forsteri ethanolic (ePE) and cyclohexane (cPE) plant extract on LPS-induced human macrophages models and quantified cytokines and quinolinic acid (QUIN) as inflammatory markers. Our results show that extract of ePE and cPE significantly inhibit inflammatory cytokine IL-6 and TNF-α induced by LPS on PMA-derived THP-1 macrophages. QUIN production is also diminished under ePE and cPE treatment in activated human monocyte-derived macrophages (MDMs). Seven abietane diterpenes were characterized from C. forsteri cPE including coleon U (1), coleon U-quinone (2), 8α,9α-epoxycoleon U-quinone (3), horminone or 7α-hydroxyroyleanone (4), 6β,7α-dihydroxyroyleanone (5), 7α-acetoxy-6β-hydroxyroyleanone (6) and 7α-formyloxy-6β-hydroxyroyleanone (7). We discussed potential contributions of these molecules from C. forsteri extracts for their anti-inflammatory activities.